Encrypted Color Image Transmission in LQ-based GSIC Pre-coded Multiuser Downlink Wireless Communication System - FARUK, MD OMOR; Ullah, Shaikh Enayet (European Journal of Applied Sciences, 2019)
The use of LQ-Based GSIC pre-coding scheme in next generation cellular mobile network can be a robust and effective technique for unique cancellation of multiuser interference. In 5G/beyond 5G a great emphasis is being given on ensuring physical layer security. In this paper, an investigative study has been made on the performance evaluation of encrypted color image transmission in LQ-based GSIC pre-coded multiuser downlink wireless communication system. The 6×2 multi-antenna configured simulated system under investigation incorporates SPC (3, 2) channel coding, low order digital modulations (QAM, QPSK, DQPSK), DNA and sine map based RGB image encryption and Zero Forcing (ZF) signal detection techniques. In the scenario of encrypted multiuser color image transmission over AWGN and Rayleigh fading channels, it is observable that the simulative system is very much effective and robust in retrieving color image for each of the three users under a moderate signal to noise ratio of 10 dB.